2009
DOI: 10.1021/pr800799s
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic Analysis of Oil Mobilization in Seed Germination and Postgermination Development of Jatropha curcas

Abstract: To understand oil mobilization in germinating seeds, we performed ultrastructural observation and proteomic analysis of endosperm in germinating Jatropha curcas seeds. Results showed that the oil mobilization was initiated during germination, and then the oil was consumed for early seedling development. The significant change in abundance of 50 protein spots during germination indicated that several pathways including beta-oxidation, glyoxylate cycle, glycolysis, citric acid cycle, gluconeogenesis, and pentose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
62
0
6

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(73 citation statements)
references
References 40 publications
5
62
0
6
Order By: Relevance
“…Recently, candidate genes involved in fatty acid biosynthesis, biotic and abiotic stress tolerance mechanisms, and regulation of secondary metabolites and phorbol esters, which are considered as important breeding targets, have been identified from whole genome sequencing analyses (Sato et al 2011), proteomics (Yang et al 2009) and transcriptomics studies (Costa et al 2010;Natarajan et al 2010;Natarajan and Parani 2011). Knowledge of their molecular functions will accelerate the process of molecular breeding of Jatropha.…”
Section: Genetic Engineering Is a Practical Technique To Improvementioning
confidence: 99%
“…Recently, candidate genes involved in fatty acid biosynthesis, biotic and abiotic stress tolerance mechanisms, and regulation of secondary metabolites and phorbol esters, which are considered as important breeding targets, have been identified from whole genome sequencing analyses (Sato et al 2011), proteomics (Yang et al 2009) and transcriptomics studies (Costa et al 2010;Natarajan et al 2010;Natarajan and Parani 2011). Knowledge of their molecular functions will accelerate the process of molecular breeding of Jatropha.…”
Section: Genetic Engineering Is a Practical Technique To Improvementioning
confidence: 99%
“…Aunque en los últimos diez años se ha incrementado sustancialmente el número de investigaciones con la planta J. curcas (Achten et al, 2010;Carels, 2013), impulsado por el interés en la obtención de materia prima para fabricar biocombustibles, se ha dado poca atención al estudio microscópico de los oleosomas de la semilla. Los estudios de proteómica de los oleosomas de J. curcas son abundantes Ming-Feng et al, 2009;Mao-Sheng et al, 2011;Popluechai et al, 2011), sin embargo, solo dos reportes se enfocaron en el análisis de los oleosomas por sí mismos (Gu et al, 2012;Ishii et al, 2013).…”
Section: Discussionunclassified
“…A recent study to understand oil mobilization in germinating seeds, proteomic analysis of endosperm clearly showed that oil mobilization that was initiated during germination was used up for early seedling development [50]. Several pathways including b-oxidation, glyoxylate cycle, glycolysis, citric acid cycle, gluconeogenesis, and pentose phosphate pathway were involved in the oil mobilization.…”
Section: Future Perspectives and Conclusionmentioning
confidence: 99%